Magnetic resonance imaging as a non‐invasive tool to assess gastric emptying in mice. Issue 2 (13th November 2022) - Chavero‐Pieres, Marta; Viola, Maria Francesca; Appeltans, Iris; Abdurahiman, Saeed; Gsell, Willy; Matteoli, Gianluca; Himmelreich, Uwe; Boeckxstaens, Guy
Abstract: Background: Methods to study gastric emptying in rodents are time consuming or terminal, preventing repetitive assessment in the same animal. Magnetic resonance imaging (MRI) is a non‐invasive technique increasingly used to investigate gastrointestinal function devoid of these shortcomings. Here, we evaluated MRI to measure gastric emptying in control animals and in two different models of gastroparesis. Methods: Mice were scanned using a 9.4 Tesla MR scanner. Gastric volume was measured by delineating the stomach lumen area. Control mice were scanned every 30 min after ingestion of a 0.2 g meal and stomach volume was quantified. The ability of MRI to detect delayed gastric emptying was evaluated in models of morphine‐induced gastroparesis and streptozotocin‐induced diabetes. Key Results: Magnetic resonance imaging reproducibly detected increased gastric volume following ingestion of a standard meal and progressively decreased with a half emptying time of 59 ± 5 min. Morphine significantly increased gastric volume measured at t  = 120 min (saline: 20 ± 2 vs morphine: 34 ± 5 mm 3 ; n  = 8–10; p  < 0.001) and increased half emptying time using the breath test (saline: 85 ± 22 vs morphine: 161 ± 46 min; n  = 10; p  < 0.001). In diabetic mice, gastric volume assessed by MRI at t  = 60 min (control: 23 ± 2 mm 3 ; n  = 14 vs diabetic: 26 ± 5 mm 3 ; n  = 18; p  = 0.014) but not at t  = 120 min (control: 21 ± 3 mm 3 ; n  = 13 vs diabetic: 18 ± 5 mm 3 ; n  = 18; p  = 0.115) was significantly increased compared to nondiabetic mice. Conclusions and Inferences: Our data indicate that MRI is a reliable and reproducible tool to assess gastric emptying in mice and represents a useful technique to study gastroparesis in disease models or for evaluation of pharmacological compounds. Abstract : Our data indicate that MRI is a reliable and reproducible tool to assess gastric emptying in mice and represents a useful technique to study gastroparesis in disease models or for evaluation of pharmacological compounds.